Investigation of Adsorption of Metal Ions on Polystyrene Divinyl Benzene Copolymers byScanning Electron Microscopy and Flame Atomic Absorption Spectrometry - Soylak, Mustafa; Saracoglu, Sibel; Elci, Latif (Asian Journal of Chemistry, 2016)
The adsorptions of some metal ions as chelates or complexes on two polystyrene divinyl benzene copolymers (amberlite XAD-1180 and ambersorb 563) were examined for preconcentration-separation of trace heavy metal ions. Flame atomic absorption spectrometry (FAAS) and scanning electron microscope (SEM) were used in the identification of the adsorption of metal ions on the resins. The optimal analytical conditions for the quantitative adsorption and recoveries of the heavy metal ions on ambersorb 563 and amberlite XAD-1180 were discussed.